Assessment Of The Level Of Creative Leadership Among Administrative Leaders In The Directorates Of Youth And Sports In The Central And Southern Regions - Saadoun Qasim Lazim (Journal of Education and Sport Science, 2026)
The importance of this research lies in evaluating the level of creative leadership among the administrative leaders of the youth and sports directorates in the central and southern regions. The research problem was that creative leadership is the optimal way to confront these challenges. A humanitarian necessity and a historical imperative for any institution, this is the cornerstone for developing and implementing strategies through which goals can be achieved. It is essential to ensure the suitability of the chosen strategy, and this requires those involved in the institutions to... Sports have garnered significant attention for guiding these strategies in all aspects and specific situations. From this perspective, the problem addressed in this study is formulated by seeking the answer to the following logical question: "Evaluating the level of The creative leadership of the administrative leaders of the youth and sports directorates in the central and southern regions is good. The research aims to develop a scale for creative leadership among the administrative leaders of the youth and sports directorates in the central region. The study aimed to identify the level of creative leadership among administrative leaders of youth and sports directorates in the central and southern regions. The researcher chose the descriptive survey method to suit the nature of the research, and a sample was selected. The purposive research was conducted among general managers, department heads, division heads, and unit heads in the Youth and Sports Directorate in the Central and Southern regions for the year 2025-2026. The research sample consisted of (238) individuals, representing (100%) of The population consisted of (238) individuals. The questionnaire was distributed to the sample and retrieved by the researcher. The exploratory experiment sample consisted of (10) administrators. The construction sample included the construction team. The sample, selected using stratified random sampling (proportional sampling), consisted of (100) administrators. The main application sample included (128) administrators. One of the most important conclusions was the development of two leadership scales. Creative administrators of the youth and sports directorates in the central and southern regions.